Domestic Anti-Avoidance Legislation in Relation to Tax Treaty Law - Asllani, Shkumbin (European Journal of Multidisciplinary Studies, 2017)
In today’s international taxation most of the developing countries enter into tax treaties which are drafted in line with the OECD MC to eliminate double taxation. Yet, is well-known fact that tax treaties in practice are abused by tax payers, therefore, majority of states have introduce legislation specifically designed to prevent tax avoidance and protect their domestic interests. In legal practice and literature the act of overriding international tax treaties and denying treaty benefits in favour of domestic law provisions threatens main principle of international law and therefore is questionable to what extend the relationship between domestic law and international tax treaty agreements bridges the international norms.